Assessing the Impact of Training, Industry Partnerships, and Government Policies on the Success of Business Development Programs: A Case Study in Central Java Province - Siti Annisa Wahdiniawati; Akka Latifah Jusdienar; Afif Syarifudin Yahya; Loso Judijanto (Westscience Press, 2023)
This research explores the multifaceted factors influencing the success of business development programs in Central Java Province. Specifically, it examines the impact of training initiatives, industrial partnerships, and government policies on the participation and effectiveness of development programs. A sample of 120 businesses and entrepreneurs in the region was analyzed using structural equation modeling (SEM) with Partial Least Squares (PLS) as the data analysis method. The results reveal significant relationships between the variables under investigation. Businesses perceiving favorable government policies are more likely to participate in development programs. Likewise, investments in training programs and engagement in industry partnerships are positively associated with participation in development initiatives. The goodness-of-fit analysis demonstrates that the Estimated Model adequately represents the data, affirming its validity and reliability. The research provides valuable insights into the interconnected nature of factors contributing to the success of business development programs in Central Java Province, highlighting the importance of collaboration, supportive government policies, and training initiatives. These findings can inform policymakers, businesses, and stakeholders in the region, aiding in the design and implementation of more effective development programs.